Cyclin-dependent kinases-based synthetic lethality: Evidence, concept, and strategy - Kailin Li; Jieqiong You; Qian Wu; Wen Meng; Qiaojun He; Bo Yang; Chengliang Zhu; Ji Cao (Elsevier, 2021)
Synthetic lethality is a proven effective antitumor strategy that has attracted great attention. Large-scale screening has revealed many synthetic lethal genetic phenotypes, and relevant small-molecule drugs have also been implemented in clinical practice. Increasing evidence suggests that CDKs, constituting a kinase family predominantly involved in cell cycle control, are synthetic lethal factors when combined with certain oncogenes, such as MYC, TP53, and RAS, which facilitate numerous antitumor treatment options based on CDK-related synthetic lethality. In this review, we focus on the synthetic lethal phenotype and mechanism related to CDKs and summarize the preclinical and clinical discoveries of CDK inhibitors to explore the prospect of CDK inhibitors as antitumor compounds for strategic synthesis lethality in the future.